Molecular biology of the cell : the problems book - Wilson, John H; Hunt, Tim (Garland, 1994)
Designed to help students appreciate the ways experiments and simple calculations lead to an understanding of how cells work. Provides a rehearsal of key terms, tests for understanding basic concepts, and research-based problems.
Keywords: biologie